The Effect of SAQ on Developing Some Special Abilities in Young Boxers - Jalil, Eabd; Majee, Ali (Journal of Physical Education, 2019)
Analysis of boxing sports shows that boxers need all physical and motor abilities in varied proportions according to the type of performance, manner of play as well as the time of each round and type of opponent. This exchange between defense and offense during the match requires the boxer to have special physical and motor abilities not found in other sports.  The researchers aimed at answering the following questions: can special abilities be developed using SAQ training? The researchers used the experimental method on (20) boxers aged 14 – 16 years old from national center for gifted in boxing. The results showed that SAQ training develop special abilities in boxers specially speed and agility.